High prevalence of somatic symptoms in a semi-rural Chilean population and its association with depression and anxiety†. Issue 4 (2nd October 2018) - Sandaña, Carlos; Bustos, Patricia; Amigo, Hugo; Canals, Andrea; Rona, Roberto J.
ABSTRACT: Our purpose was to study the prevalence of mental disorders with an emphasis on somatic symptoms and their association with social support in a Chilean semi-rural area. We studied a sample of 796 adults born between 1974 and 1978 in Limache, Chile. The Patient Health Questionnaire-9, the Generalized Anxiety Disorder-7, the Patient Health Questionnaire-15 and the Medical Outcomes Study Social Support Scale test were used to assess depression, anxiety, somatic symptoms and social support, respectively. We found that the prevalence of psychosomatic symptoms was 63.8% in women (most of them in the severe range) and 34.1% in men. The rates of depression and anxiety were 17.7 and 21.7%, respectively. Psychosomatic symptoms were strongly associated with depression (male OR:10.33, CI 95%:2.91–34.54; female OR:6.19, CI 95%:2.64–14.52) and anxiety (male OR:2.63, CI 95%:1.04–6.63; female OR:3.97, CI 95%:2.02–7.78). The association between psychosomatic symptoms and functional impairment was mainly due to symptoms of depression and anxiety. Mental disorders were inversely associated with social support. We conclude that psychosomatic symptoms were the norm, especially in women. Social support is marginally lower in those with a mental disorder, but still perceived as high. Physical complains in these communities are frequently the expression of depression and anxiety.